2015
DOI: 10.1002/ange.201505464
|View full text |Cite
|
Sign up to set email alerts
|

A Stimuli‐Responsive Rotaxane–Gold Catalyst: Regulation of Activity and Diastereoselectivity

Abstract: Arotaxane-based Au catalyst was developed and the effect of the mechanical bond on its behavior was studied. Unlike the non-interlocked thread, the rotaxane requires ac atalytically innocent cofactor,t he identity of which significantly influences both the yield and diastereoselectivity of the reaction. Under optimizedc onditions,A u I (the catalyst), Ag I (to abstract the Cl À ligand), and Cu I (the cofactor) combine to produce acatalyst with excellent activity and selectivity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
15
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 67 publications
(15 citation statements)
references
References 76 publications
0
15
0
Order By: Relevance
“…Encapsulation of a gold metal center into a cavity appears interesting because it allows variation of the reactivity in catalysis. [79][80][81][82][83][84] Therefore, we anticipated that modularity of the cavity shape should affect the outcomes of the reactions in terms of regio-and stereoselectivity. We previously showed that (a-ICyD)AuCl and (b-ICyD)AuCl were able to catalyze cycloisomerization reactions.…”
Section: Can We Connect the CD Shape To Selectivity In Metal-catalyzementioning
confidence: 99%
“…Encapsulation of a gold metal center into a cavity appears interesting because it allows variation of the reactivity in catalysis. [79][80][81][82][83][84] Therefore, we anticipated that modularity of the cavity shape should affect the outcomes of the reactions in terms of regio-and stereoselectivity. We previously showed that (a-ICyD)AuCl and (b-ICyD)AuCl were able to catalyze cycloisomerization reactions.…”
Section: Can We Connect the CD Shape To Selectivity In Metal-catalyzementioning
confidence: 99%
“…For these reasons, MIMs can be regarded as appealing systems for investigating allosteric communication mechanisms and implementing them within synthetic species to achieve functions (11). Nevertheless, studies of allosteric effects in rotaxanes and catenanes are rare (12) and have been limited so far to a pioneering work by Sauvage and coworkers (13) and, more recently, to the realization of stimuli-responsive switches (14, 15) for controlling catalytic functions (16)(17)(18)(19)(20).In a recent investigation of a family of [2]rotaxanes (21) we showed quantitatively that the acidity of an ammonium ion on the axle is strongly depressed when it is surrounded by a crown ether ring, for which it is an efficient recognition motif (8). Such a phenomenon, that can be rationalized with both thermodynamic and kinetic arguments, is in line with earlier observations (22-26) that deprotonation of ammonium axles in crown etherbased rotaxanes is extremely difficult to achieve.…”
mentioning
confidence: 99%
“…For these reasons, MIMs can be regarded as appealing systems for investigating allosteric communication mechanisms and implementing them within synthetic species to achieve functions (11). Nevertheless, studies of allosteric effects in rotaxanes and catenanes are rare (12) and have been limited so far to a pioneering work by Sauvage and coworkers (13) and, more recently, to the realization of stimuli-responsive switches (14, 15) for controlling catalytic functions (16)(17)(18)(19)(20).…”
mentioning
confidence: 99%
“…[4] Thea ctive template (AT) approach to interlocked molecules, [5] introduced by Leigh and co-workers,h arnesses the ability of endotopic functional groups within amacrocycle to mediate an ew covalent bond forming reaction through the ring and thus generate amechanical bond. Thefirst and best studied AT process is the AT-CuAACr eaction, [6] which employs an endotopically ligated Cu I ion and inherits the benefits of the parent CuAACp rocess to produce complex rotaxanes, [7] catenanes, [8] and knots [9] in excellent yield with broad substrate scope,a nd has been applied to the synthesis of mechanically interlocked ligands, [10] pro-drugs, [11] catalysts, [12] hosts, [13] sensors, [14] and molecular machines. [15] However,t odate,a ll AT reactions generate products in which the bond forming reaction used determines the functional group present in the product;all AT-CuAACproducts reported retain the 1,2,3-triazole link produced in the cycloaddition process.Here we report the unexpected observation and subsequent optimization of ad omino AT-CuAACrearrangement process to produce acrylamide-derived rotax-anes with up to 100 %selectivity,and mechanistic studies that rationalize the reaction outcome.N ot only does this new transformation expand the range of interlocked molecules available using this simple methodology,i ta lso serves to highlight the ability of mechanical bonding to augment chemical reactivity to produce new reaction outcomes.…”
mentioning
confidence: 99%